Pengaruh Good Corporate Governance terhadap Nilai Perusahaan yang dimediasi oleh Return on Asset pada Perusahaan Sektor Healthcare yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Anzani, Leni; Simatupang, Frido Saritua (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the influence of GCG on company value and its indirect influence through Return on Assets (RoA). The research sample consisted of 15 Healthcare sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period, with data analysis techniques using path analysis. The research results show that the variable size of the board of commissioners, board of directors and institutional ownership on RoA has no influence on Tobin's Q, while RoA on Tobin's Q has a positive influence. In addition, RoA is unable to mediate the influence of the size of the board of commissioners, board of directors and institutional ownership on Tobin's Q.